2017
DOI: 10.1016/j.scitotenv.2017.03.223
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopic composition of perchlorate and nitrate accumulated in plants: Hydroponic experiments and field data

Abstract: Natural perchlorate (ClO) in soil and groundwater exhibits a wide range in stable isotopic compositions (δCl, δO, and ΔO), indicating that ClO may be formed through more than one pathway and/or undergoes post-depositional isotopic alteration. Plants are known to accumulate ClO, but little is known about their ability to alter its isotopic composition. We examined the potential for plants to alter the isotopic composition of ClO in hydroponic and field experiments conducted with snap beans (Phaseolus vulgaris L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In plants, significant enrichment in both 15 N and 18 O is observed in the NO3extracted from leaves after uptake relative to the NO3from water, but the changes in the NO3isotopic composition in the water are minor (Estrada et al, 2017;Spoelstra et al, 2010). Therefore, the NO3isotopic characterization of water samples collected at the CW might improve the understanding and support the evaluation of the performance of the remediation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, significant enrichment in both 15 N and 18 O is observed in the NO3extracted from leaves after uptake relative to the NO3from water, but the changes in the NO3isotopic composition in the water are minor (Estrada et al, 2017;Spoelstra et al, 2010). Therefore, the NO3isotopic characterization of water samples collected at the CW might improve the understanding and support the evaluation of the performance of the remediation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, variations of δ 18 O‐NO 3 − and δ 15 N‐NO 3 − are mainly influenced by NO 3 − reduction (NR) into NH 4 + in the protein‐making process (Tcherkez & Farquhar, ). Laboratory and hydroponic experiments on NR‐induced isotopic fractionation showed that δ 18 O‐NO 3 − and δ 15 N‐NO 3 − co‐vary along a 1 : 1 slope (Karsh et al ., ; Estrada et al ., ). These findings were supported by the only field analysis of NR fractionation, where a slope of 1.27 was found between δ 18 O‐NO 3 − and δ 15 N‐NO 3 − in tree roots (Liu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Biochemical processes such as denitrification or assimilation have also been shown in laboratory experiments to distinguishably enrich residual NO in heavier isotopes, here 15 N and 18 O (Granger et al, 2004(Granger et al, , 2010Treibergs and Granger, 2017), although this enrichment can be diluted by newly nitrified NO 3 with low N and O isotopic values (Granger and Wankel, 2016;Mayer et al, 2002). Environmental studies also reported characteristic NO 3 isotopic enrichment for denitrification (Clément et al, 2003;Fang et al, 2015;Wexler et al, 2014), assimilation (Emmerton et al, 2001;Estrada et al, 2017;X.-Y. Liu et al, 2013) or photolysis (Frey et al, 2009;Shi et al, 2015;Ye et al, 2016).…”
Section: No 3 Sources Apportionmentmentioning
confidence: 99%